The rise and fall of communism - Brown, Archie, 1938- (New York : Ecco, 2009)
The Rise and Fall of Communism explores how and why Communists came to power; how they were able, in a variety of countries on different continents, to hold on to power for so long; and what brought about the downfall of so many Communist systems.--From publisher description.
Pt. 1. Origins and development. The idea of communism ; Communism and socialism : the early years ; The Russian revolutions and civil war ; 'Building socialism' : Russia and the Soviet Union, 1917-40 ; International communism between the two world wars ; What do we mean by a communist system? -- Pt. 2. Communism ascendant. The appeals of communism ; Communism and the Second World War ; The communist takeovers in Europe : indigenous paths ; The communist takeovers in Europe : Soviet impositions ; The communists take power in China ; Post-war Stalinism and the break with Yugoslavia -- Pt. 3. Surviving without Stalin. Khrushchev and the Twentieth Party Congress ; Zig-zags on the road to 'communism' ; Revisionism and revolution in Eastern Europe ; Cuba : a Caribbean communist state ; China : from the 'Hundred Flowers' to 'Cultural Revolution' ; Communism in Asia and Africa ; The 'Prague Spring' ; 'The era of stagnation' : the Soviet Union under Brezhnev -- Pt. 4. Pluralizing pressures. The challenge from Poland : John Paul II, Lech Wałesa, and the rise of solidarity ; Reform in China : Deng Xiaoping and after ; The challenge of the West -- Pt. 5. Interpreting the fall of communism. Gorbachev, Perestroika, and the attempt to reform communism, 1985-87 ; The dismantling of Soviet communism, 1988-89 ; The end of communism in Europe ; The break-up of the Soviet state ; Why did communism last so long? ; What caused the collapse of communism? ; What's left of communism?
Includes bibliographical references (p. [623]-688) and index.
Keywords: Communism -- History